Activization of word-formation potential of non-derivative verbs with root morpheme of Latin origin in the modern Russian language - Stryha, Katsiaryna V. (Journal of the Belarusian State University. Philology, 2019)
Quantitative and structural-semantic analysis of new words, both directly and indirectly motivated by non-derivative verbs with root morpheme of Latin origin and fixed in dictionaries of the turn of XX–XXI century, but absent in the composition of the corresponding word-formation nests in the «Word-Formation dictionary of the Russian language» of A. N. Tikhonov is carried out. It is established that in the period of the end of the XX – the beginning of the XXI centuries 52 % of the analyzed deverbal nests expanded their composition, as a result of which the derivational capacity of non-derivative Latin-speaking verbs increased from 8.8 to 10.4. It is specified that the main number of new words are nouns and (to a lesser extent) the adjectives of the second – the third stages of derivation. It is determined that the most relevant ways of formation of new words are addition and (less often) suffixation. The attention is focused on the fact that the factor of the ambiguity of the motivator has a positive impact on the realization of its word-formative potential. Some selectivity of the use of primordial and borrowed affixes in the formation of derivatives of a certain part of speech and a certain word-formative meaning is revealed.